Inexplicable voices: liminal whiteness in Antebellum American fiction - Murray, Hannah Lauren (2017)
This thesis examines the repeated appearance of liminal white voices in antebellum American fiction. It identifies a number of white characters who inhabit the boundary between life and death and produce inexplicable voices: talking corpses, ghosts, ventriloquists, spiritualist mediums and non-human bodies. It argues that Charles Brockden Brown, Washington Irving, Robert Montgomery Bird, Edgar Allan Poe, Nathaniel Hawthorne and Herman Melville continually associate dead, dying and supernatural white figures with African Americans and Native Americans to amplify these white characters own marginal positions within their communities. While existing criticism classifies the non-white and female body as a site of otherness, this thesis identifies marginality within the white male citizen himself. The six chapters examine how authors articulate liminal whiteness in different vocal contexts: ventriloquism in Brown, storytelling in Irving, blackface minstrelsy in Bird, medical discourse in Poe, enchanting speech in Hawthorne, and wordlessness in Melville. Across these texts, the liminal figure’s voice disturbs essentialist racial ideologies and challenges prescriptions of citizenship in the antebellum period. Inexplicable voices act as powerful articulations of liminal whiteness that question, contest or negate antebellum ideals of the autonomous, rational, industrious, social and respectable white citizen. This thesis demonstrates that antebellum authors employ liminal white voices across the border of life and death to both explore and attempt to contain threats and anxieties of fragile or negated white citizenship. In doing so, this thesis contributes to a growing body of scholarship concerned with the cultural construction of whiteness and citizenship in the antebellum period.